Pré-posicionamento e aquisição de suprimentos na cadeia humanitária brasileira - García Pérez, Andrés Felipe (2018)
In the Brazilian humanitarian chain, product flows from the private sector to victims of disasters are only allowed on the hypothesis that a bidding process with the public sphere was carried out. The proposal of this work is a mixed-integer linear programming approach, for the supply of aid in disaster areas via acquisition and / or pre-positioning, with the purpose of integrating location of deposits decisions and evaluating the trade-off between the aids bought before and after the disaster, from the agreements between suppliers and the Brazilian Civil Defense. Location of deposits is treated under a localization approach of maximum coverage with the time of attendance to the victims being a limiting factor. Beyond location of deposits, is also considered its size to be opened. There are considered restrictions of geographical and product fairness, for a fair distribution of a budget available, common in the governmental scope. Results shows the need to maintain strategic stocks in certain Brazilians states, guaranteeing time satisfaction in emergencies products according to the stablished parameters.